Utilization Of Hydroponic Technique For Potato Mini -Tubers Production (Journal of Pharmaceutical Negative Results, 2023)
The production of potato seeds in Egypt is the nucleus for providing the import of seeds as potatoes are the fourth most important crop in the world and Egypt imports a large number of potato seeds at high costs. This study aims to optimize the water productivity of the hydroponic and aeroponic systems and increase the potato crop yield and quality. The current experiment was carried out in a greenhouse (1.2 hectares) at the National Company for Protected cultivation, Mohammed Naguib Military Base, Egypt. During the period from 15/2/2019 to 1/6/2019 and 15/9/2019 to 1/1/2020. The experimental layout included some engineering factors of hydroponic and aeroponic systems such as density of plants /per square meter and different nozzles with different discharges for sprinkler and dripper systems. In addition to the determination of water productivity in hydroponic and aeroponic systems. The highest yield production for aeroponic system was at discharge 1.2 lph for micro tuber and mini tuber was as follow; 180 tuber / square meter. aeroponic system was better than the hydroponic system by a percentage of 21% for several mini-tubers per square meter and the yield productivity of the mini-tubers was 93.7%.  Aeroponics system gave the highest production at density 100 tuber /m2 for micro and mini tuber were: 500 tubers/m2 and 610 tubers/m2, respectively, and in the hydroponic system, micro tuber and mini tuber were 300 tubers/m2 and 480 tubers/m2, respectively.